(untitled) (Economic and Political Thought, 2023)
This study aims to answer the question contained in its title: Can the Road and Belt project be an alternative to the current global flow routes? The logical axis of the article is the role of the logistics system in the competitiveness of countries and the effectiveness of projects such as BRI. The article is a literature review. The article contains an introduction that discusses the history of the BRI initiative and its main conditions. The first chapter presents the concept of the country’s logistics system and its impact on the country’s economic competitiveness. The second chapter discusses the development of China’s logistics system, which is the initial phase initiating the BRI project. Chapter three discusses China’s investments in BRI member countries, with particular emphasis on transport and logistics projects. The article ends with final conclusions.